More than a gut feeling: What is the role of the gastrointestinal tract in female athlete health? - Pugh, J. N.; Lydon, K.; O`Donovan, C. M.; O`Sullivan, O.; Madigan, S. M. (European Journal of Sport Science, 2022)
As with much of science, the female athlete is under researched, particularly in the area of gastrointestinal (GI) physiology. Gut function is of pivotal importance to athletes in that it supports digestion and absorption of nutrients, as well as providing a barrier between the external environment and the circulation. While sex-derived differences in GI structure and function have been well characterised at rest, there remains a paucity of data examining this during exercise. The wider impact of the GI system has begun to be realised and it is now widely acknowledged to play a role in more systemic bodily systems. In the current review, we discuss localised issues including the GI structure, function, and microbiome of male and females. We also discuss GI-related symptoms experienced by athletes, highlight the differences in incidence between males and females, and discuss contributing factors. We then move beyond the gut to discuss wider biological processes that have been shown to have both sex-related differences and that are impacted by the GI system. Some of these areas include immune function and risk of illness, sleep, hormones, bone health and the gut-brain-axis. The magnitude of such effects and relationships is currently unknown but there is enough mechanistic data for future studies to consider a more central role that the gastrointestinal tract may play in overall female athlete health.